Impacts of Green Facades in Modern Era - Aaryaman Singh; Avitesh Vaishnavi Nayak (International Journal of Environmental Planning and Development Architecture, 2023)
Modern architecture was an architectural movement or style centred on cutting-edge construction technologies, particularly the use of reinforced concrete, glass, and steel. The foundational goal of 21st century architecture is to create better structures that are inherently sustainable by utilising better materials and technologies. Facades are the outermost covering of a building which have the maximum interaction with the environment. A wall that is completely or partially covered with vegetation is known as a green façade. Green facades enhance the urban environment in terms of economy, environment, aesthetics, and physiology. There are many aspects associated with the built environment such as energy efficiency, pollution levels and ecological responsiveness, these issues need to be addressed to create element of the built of the modern environment. Analysing of different type of façade systems can lead towards a complex dynamic sustainable facades system that not just acts as the skin of the building but performs more functions. This study talks about the integration of modern architecture with green facades and the impacts of green facades in different climatic conditions. Outcomes of this study will be helpful to understand modern green facade systems and exploring new design innovations for a better and more efficient future.
Keywords: Green Facades; Modern Architecture; Modern Façade Systems; Sustainable Buildings; energy efficiency